EXPLORING THE STICKY COSTS THEORY: TRENDS, CHALLENGES, AND INSIGHTS - Lucas, A.; Azevedo, G.; Oliveira, J.; Santos, L.L. (16th International Conference on Education and New Learning Technologies, 2024)
Over the past few decades, there has been a remarkable growth in the body of scientific literature on accounting. The sharing of research findings through publications stands as a crucial driver in propelling the field of accounting forward. These publications play a vital role in delivering new perspectives and breakthroughs to researchers, accounting professionals, managers, and a wider global audience. Many companies’ managers, and even accountants, follow the traditional theories, that divide costs only into fixed and variable. Variable costs, dependent on a company's activity, and fixed costs, which remain constant regardless of activity levels, are traditionally taught and understood. Yet, recent studies reveal evidence of the existence of sticky costs—costs that increase more with activity increases than they decrease with activity decreases. This phenomenon underscores the need for a deeper understanding of cost behavior, particularly in managerial decision-making. This study adopts a document analysis method to examine literature from 2010 to 2023, based on articles from the B-On, focusing on the concept of sticky costs. Notably, despite its relevance to effective cost management, the topic of sticky costs has not found its place in academic curricula. This gap is significant, as the inclusion of sticky costs in educational programs can better equip future professionals with essential analytical skills and a nuanced understanding of financial management principles. By addressing this gap, our research aims to contribute to the enhancement of educational curricula, aligning with broader educational objectives. These objectives include fostering critical thinking, enhancing decision-making capabilities, and equipping students with practical knowledge essential for navigating complex business environments. Furthermore, the incorporation of sticky costs into academic curricula is not only academically enriching but also aligns with global objectives, such as the United Nations Sustainable Development Goal 8, promoting sustainable economic growth through effective management practices. In conclusion, this study serves as a call to action for academia to reconsider the inclusion of sticky costs in educational curricula. By doing so, educational institutions can better prepare students for the dynamic challenges of the modern business landscape, ultimately contributing to the cultivation of skilled and responsible future business leaders. Managers with knowledge of the sticky costs’ behavior will reduce the impact of setbacks on the sustainability of companies.